Adab Konstitusi; Upaya Meluruskan Kesesatan Pikir Konstitusi - Yogi Prasetyo (Justitia Jurnal Hukum, 2017)
The Constitution as the legal basis for formation of legislation in the system of Indonesia. The misuse of the constitution (UUD 1945) by the political interests of goverment caused mislead and made the situation of the nation getting worse. Liberal capitalistic value wrapped in modern positivistic legal system that puts the ratio had diverge from culture constitution. needs to be clarified with the balance of conscience through culture constitution. Culture constitution is a constitutional concept who saw citizen of Indonesia as creatures of God by virtue of intelligence and unseen. So with that constitution is formed, conceived and executed to be qualified and to bring the benefit of the world and the hereafter.